The effect of hand and foot exercises training on symptoms of numbness in colorectal cancer patients receiving oxaliplatin via peripheral intravenous administration - Introntakun, kampon; Silaguntsuti, Chureeporn; Vittayatigonnasak, Arveewan; Jamparsi, Supapan; Boonyopragarn, Pichaya; Mamah, Methina; Pairat, Kortchakorn; Amsup3, Nathapong; Parklug, Piyarat (Vajira Nursing Journal, 2024)
This experimental study aims to examine the effect of hand and foot exercise training on numbness symptoms in colorectal cancer patients receiving oxaliplatin via peripheral intravenous administration. The sample comprises patients diagnosed with colorectal cancer who receive care at Mahavajiravudh Ward 6A of Vajira Hospital. A total of 52 eligible participants were selected using a block selection method and divided into two groups of 26 participants each. The control group received standard nursing care, while the experimental group participated in hand and foot exercise training. Numbness symptoms were assessed using a measurement tool developed from a review of relevant literature. Data analysis included descriptive statistics, such as percentage, mean, and standard deviation, along with t-tests for hypothesis testing and analysis of covariance (ANCOVA) to assess variance The research results revealed that pre-exercise numbness scores significantly influenced post-exercise numbness scores (F(1, 49) = 164.12, p < .001). After adjusting for the effect of pre-exercise scores, the experimental group that received hand and foot exercise training showed a statistically significant reduction in post-exercise neuropathy symptoms compared to the control group (F(1, 49) = 39.81, p < .001). This study indicates that hand and foot exercise training can effectively alleviate numbness symptoms associated with oxaliplatin treatment in colorectal cancer patients.